2003
DOI: 10.1046/j.1460-9568.2003.02691.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of auditory deprivation upon the tonopic organization in the inferior colliculus: a Fos immunocytochemical study in the rat

Abstract: The frequency organization in the inferior colliculus of neonatally-deafened rats was investigated using electrical stimulation of the cochlea and immunoreactivity for Fos as a marker of neuronal activity. An electrode implanted either at the base or at the apex of the right cochlea delivered a unique 45-min stimulation at two different level intensities and at two time points, i.e. either at 4 weeks or at 4 months. In 4-week-old rats stimulated at 5x threshold, a site-for-site organization was observed since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…8). Under these circumstances, the reduction in c‐Fos expression could be similar to effects observed with auditory deprivation in juvenile rats (Wu et al, 2003a). Wu et al sound deprived juvenile rats and then sound stimulated them later at two time points, 4 weeks or 4 months.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…8). Under these circumstances, the reduction in c‐Fos expression could be similar to effects observed with auditory deprivation in juvenile rats (Wu et al, 2003a). Wu et al sound deprived juvenile rats and then sound stimulated them later at two time points, 4 weeks or 4 months.…”
Section: Discussionsupporting
confidence: 66%
“…Wu et al sound deprived juvenile rats and then sound stimulated them later at two time points, 4 weeks or 4 months. They found changes in c‐Fos expression in terms of both location and number of c‐Fos‐expressing cells within the CIC (Wu et al, 2003a). In our experimental paradigm, the establishment of a chronic oxidative stress within the cochlea causes the attenuation of the amplitude of the eighth cranial nerve, and as a consequence there is a decreased c‐Fos expression in the CIC in animals chronically exposed to CO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other animal models, cochlear implantation in the rat is considered surgically difficult, and while there are a number of acute studies in this species (Nagase et al, 2000;Wu et al, 2003;Hsu et al, 2001;Vischer et al, 1997;Paolini and Clark, 1998;Shepherd et al, 2004), there has been no chronic cochlear implantation reported. The reasons for this difficulty includes: i) relatively smaller size of the rat cochlea; ii) the difficulty in developing such a small multiple channel scala tympani electrode array; and iii) the presence of the stapedial or pterygopalatine artery (SA), located in the middle ear cavity (Govaerts et al, 1993;Judkins and Li, 1997;Praetorius et al, 2001;Pinilla et al, 2001;Yamamoto et al, 2003), severely reducing surgical access to the scala tympani.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss was evaluated by the pinna reflex and clickevoked auditory brainstem responses (ABR), as previously described [21]. ABRs were recorded at the end of treatment.…”
Section: Auditory Brainstem Response (Abr)mentioning
confidence: 99%